Current Perspective of Diagnostic and Treatment of Rhinitis: A Literature Review - Karenina, Lovenita Visca; Pujiastuti, Agustina Tri (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
ABSTRACT Background: Rhinitis is an inflammation or irritation of the nasal mucosa that characterized by symptoms such as runny nose, nasal congestion, and sneezing. This condition can also be caused by inflammation of eyes, ears, and throat. Objective: To review the literature on vasomotor rhinitis, allergic rhinitis, the relationship between rhinitis and students’ quality of life, and rhinitis in sports athletes. Methods: This literature review was conducted by selecting a topic and determining keywords for journal searches using English and Indonesian through several databases including Google Scholar and NCBI Bookshelf. Results: This literature review shows that vasomotor rhinitis and allergic rhinitis have different causes and treatments, although both show similar symptoms. Conclusion: This literature review shows that vasomotor rhinitis and allergic rhinitis have different causes and treatments, although both show similar symptoms. Keywords: Allergic rhinitis, vasomotor rhinitis